2015
DOI: 10.1186/s12348-015-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of changes in quality of life among patients in the SAVE Study - Sirolimus as therapeutic Approach to uVEitis: a randomized study to assess the safety and bioactivity of intravitreal and subconjunctival injections of sirolimus in patients with non-infectious uveitis

Abstract: BackgroundThe National Eye Institute 39-Question Visual Function Questionnaire (NEI VFQ-39) is an indicator of vision-related quality of life (QoL). The NEI VFQ-39 is used to assess the QoL in patients with non-infectious posterior uveitis, intermediate uveitis, or panuveitis, treated with subconjunctival (SCJ) or intravitreal (IVT) sirolimus as an immunomodulatory therapeutic (IMT) agent, delivered subconjunctivally (SCJ) or intravitreally (IVT) (the SAVE Study). Thirty subjects with non-infectious uveitis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
0
13
0
2
Order By: Relevance
“…The use of intravitreal and subcutaneous administration of sirolimus was investigated in two prospective studies. The SAVE study [40,41,42] was a randomised open label trial comparing two monthly subcutaneous vs intravitreal sirolimus with a primary endpoint at 6 months, and then a further 6 months extension during which treatment could be continued at the investigator's discretion. The primary efficacy outcome was a reduction of vitreous haze by 2 points (in those with active uveitis at baseline), or the maintenance of no clinical vitreous haze (in those with inactive disease at baseline).…”
Section: Intravitreal and Subcutaneous Injection Of Sirolimusmentioning
confidence: 99%
“…The use of intravitreal and subcutaneous administration of sirolimus was investigated in two prospective studies. The SAVE study [40,41,42] was a randomised open label trial comparing two monthly subcutaneous vs intravitreal sirolimus with a primary endpoint at 6 months, and then a further 6 months extension during which treatment could be continued at the investigator's discretion. The primary efficacy outcome was a reduction of vitreous haze by 2 points (in those with active uveitis at baseline), or the maintenance of no clinical vitreous haze (in those with inactive disease at baseline).…”
Section: Intravitreal and Subcutaneous Injection Of Sirolimusmentioning
confidence: 99%
“…The 1‐year outcome of the SAVE study was positive with 70% of the patients showing a more‐than‐two‐step reduction in the vitreous haze score . The subjects in the SAVE study also showed improvement in their quality of life as assessed by the visual function questionnaire . The favourable outcome from the SAVE study was followed by the conduct of the Sirolimus as a Therapeutic Approach for Uveitis: Protocol 2 (SAVE‐2) study.…”
Section: Emerging and Adopted Therapiesmentioning
confidence: 99%
“…197 The subjects in the SAVE study also showed improvement in their quality of life as assessed by the visual function questionnaire. 198 The favourable outcome from the SAVE study was followed by the conduct of the Sirolimus as a Therapeutic Approach for Uveitis: Protocol 2 (SAVE-2) study. SAVE-2 was a phase 2 randomized open-label clinical trial evaluating two different doses of IVT sirolimus (440 μg given monthly and 880 μg given bimonthly) in patients with NIU.…”
Section: Sirolimusmentioning
confidence: 99%
“…; Vigil et al. ). In experimental autoimmune uveitis, intravitreal anti‐TNF administration suppresses ocular inflammation particularly inhibiting macrophage activation that suppresses structural damage and prevents functional loss.…”
Section: Introductionmentioning
confidence: 98%
“…Side-effects related to systemic administration have led to the investigation of intravitreal route of administration, as an option that could curtail some of these unwanted effects while preserving therapeutic efficacy (Levy-Clarke et al 2014;Pascual-Camps et al 2014). This route of drug delivery has been well established in uveitis treated with corticosteroids (Kane et al 2008;Taylor et al 2012;Kempen et al 2015a,b;Reddy et al 2016), anti-vascular endothelial growth factor (VEGF), (Androudi et al 2010;Tempest-Roe et al 2013) or sirolimus (Ibrahim et al 2015;Vigil et al 2015). In experimental autoimmune uveitis, intravitreal anti-TNF administration suppresses ocular inflammation particularly inhibiting macrophage activation that suppresses structural damage and prevents functional loss.…”
Section: Introductionmentioning
confidence: 99%